Neuroendocrine differentiation in non-neuroendocrine thyroid carcinoma - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1996)
Specimens from 40 cases of thyroid carcinomas, including 35 papillary, 2 follicular, 2 undifferentiated, and 1 Hurtle cell carcinoma were analyzed for neuroendocrine differentiation with immunohistochemical tests for synapthophysin, neuron-specific enolase (NSE), chromogranin, and calcitonin; all cases were stained for thyroglobulin. Histologically, none of the cases resembled a medullary carcinoma. Twenty-five percent (10 cases) were immunoreactive for one, 30% (12 cases) for two, and 15% (6 cases) for three markers. Three of the cases that were positive for all 3 markers (7.5% of all total) had diffuse strong immunoreactivity. These results demonstrated neuroendocrine differentiation may occur in non-neuroendocrine thyroid tumors and may support the postulation that endodermally derived ultimobronchial stem cells might give rise to C cells as well as follicular cells.
Keywords: MEDULLARY; ENDOCRINE